Effects of Carbon Pore Size on the Contribution of Ionic Liquid Electrolyte Phase Transitions to Energy Storage in Supercapacitors - Schutjajew, Konstantin; Yan, Runyu; Antonietti, Markus; Roth, Christina; Oschatz, Martin (Frontiers in Materials, 2019)
Recent research on ionic liquid electrolyte-based supercapacitors indicated the contribution of phase transitions of the electrolytes at high cell voltages to the energy stored. This mechanism can be exploited to significantly increase the energy density of supercapacitors, which up to now remains their major drawback. It was found that these ordering transitions require the presence of mesopores within the carbon electrode materials and that porosity in general is a key factor to trigger them, but details of the mechanism remain unexplained. To get a more profound understanding of this phenomenon, carbon materials with different pore diameters and volumes were synthesized and the effect of those properties on the phase transitions in the ionic liquids was studied by means of cyclic voltammetry. A clear correlation between the peak current and the mesopore volume is revealed and an optimal pore diameter was determined, exceeding which does not improve the phase transition behavior. These findings are useful as guidelines for the rational design of carbon mesopores in order to utilize the new energy storage modes which are neither fully capacitive, nor redox-based.